Autoimmune hepatitis: East meets west. Issue 8 (August 2015) - Yang, Fan; Wang, Qixia; Bian, Zhaolian; Ren, Lin‐Lin; Jia, Jidong; Ma, Xiong
Abstract Autoimmune hepatitis (AIH) is an inflammatory liver disease with diverse clinical spectrum, which predominantly affects females. This review provides detailed comparisons of epidemiology, genetic predispositions, clinical features, risk factors of hepatocellular carcinoma, and mortality in AIH patients between eastern and western countries. AIH prevalence and incidence are lower in Asia‐Pacific area than in Europe and America. European and American patients seem to have more severe disease, characterized with human leukocyte antigen‐DR3 haplotype, younger age, more AIH‐induced "cirrhosis" at diagnosis, higher elevated serum immunoglobulin G levels, and positive rate of antisoluble liver antigen/liver pancreatitis. The overall AIH diagnostic accuracy of revised original criteria and simplified scoring system are similar in European/American populations and Asian. Cirrhosis at presentation and non‐response to immunosuppressive therapy within 1 year are the most important predictors for poor prognosis of AIH patients.